1992
DOI: 10.1029/91jd03112
|View full text |Cite
|
Sign up to set email alerts
|

Total reactive oxidized nitrogen (NOy) in the remote Pacific troposphere and its correlation with O3 and CO: Mauna Loa Observatory Photochemistry Experiment 1988

Abstract: As part of the Mauna Loa Observatory Photochemistry Experiment (MLOPEX) total reactive oxidized nitrogen (NOy) was measured during May and early June of 1988 at the Mauna Loa Observatory, the NOAA‐Geophysical Monitoring for Climatic Change Baseline Monitoring Station, located at 3.4‐km elevation on the island of Hawaii. Gold catalytic surface conversion of individual reactive oxidized nitrogen species to NO and subsequent quantification of the NO by NO/O3 chemiluminescence was used to measure the NOy mixing ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…This is also in agreement with the conclusion drawn previously. The average CO to NO y ratios were observed to be ~26 in the most polluted and 230 in the cleanest air over rural sites in the U.S. [ Hubler et al ., ; Parrish et al ., ].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is also in agreement with the conclusion drawn previously. The average CO to NO y ratios were observed to be ~26 in the most polluted and 230 in the cleanest air over rural sites in the U.S. [ Hubler et al ., ; Parrish et al ., ].…”
Section: Resultsmentioning
confidence: 98%
“…The relationship between CO and NO y can also be used as a tracer of anthropogenic influence in different air masses [Parrish et al, 1991;Hubler et al, 1992;Stohl et al, 2002;Zellweger et al, 2003]. As the air mass ages, CO levels are expected to increase due to longer lifetime as compared to short-lived NO y .…”
Section: Correlation Analysesmentioning
confidence: 99%
“…However, these additional NO y sources are relatively small compared to surface emissions, and the result is much less NO y in the middle and upper troposphere than in the lower troposphere. The clean free troposphere has a positive ozone/NO y slope independent of stratospheric influence, but the slope increases as the stratospheric component increases [ Hübler et al , 1992; Koike et al , 1997], as evident in the middle and upper troposphere DA.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that low‐elevation air could nevertheless impact the station as a result of lifting in thermals. As one example of the apparently complex nature of the upslope flow, Hübler et al [1992] found daytime/nighttime differences in total reactive nitrogen oxides (NO y ) at MLO were smaller than expected if upslope flow simply carried MBL air to the station. They concluded that daytime air at MLO may instead be a mixture of island‐modified MBL air and FT air.…”
Section: Introductionmentioning
confidence: 96%